Effect of Annealing on the Crystallization of Poly Vinyl Chloride for Drug Delivery System - A. Abdul-Majeed, Basma; K. Hussain, Hussain; A. Kafel Al-Sultanee, Nagam (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Poly vinyl alcohol has been studied for its ability to form crystallites by using annealing method. Semicrystalline films of poly vinyl alcohol (PVA) were prepared by casting 11.5 wt. % and 13 wt. % PVA aqueous solution onto glass slides at annealing temperature range 90 -120°C and duration time 15- 60 minute. This allowed the macromolecules to form crystallites, small regions of folded and compacted chains separated by amorphous regions where single PVA chain may pass through several of these crystallites. Degree of crystallinity of PVA films (hydrogels) was determined by method of density; on the other hand the swelling behavior was conducted by the determination of water uptake, wet degree of crystallinity, gel fraction and solubility. The results of PVA films showed that water uptake decreased with increasing temperature, time of annealing and PVA concentration, while degree of crystallinity increased, and gel fraction and solubility decreased with increasing temperature and time of annealing. The maximum dry and wet degree of crystallinity was 64% and 36% respectively at 120°C and 60 min.